Big fish in big ponds: Contrast and assimilation effects on math and verbal self‐concepts of students in within‐school gifted tracks. (22nd December 2015) - Herrmann, Julia; Schmidt, Isabelle; Kessels, Ursula; Preckel, Franzis
Abstract : Background: Ability grouping can lower students' academic self‐perceptions through reference group effects of class‐average achievement on academic self‐concept (ASC) – the Big‐fish‐little‐Pond ‐effect (BFLPE; Marsh & Parker, 1984, J. Pers. Soc. Psychol ., 47, 213). Although the effect itself is well documented, many open questions remain. For instance, negative contrast effects of group average achievement and positive assimilation effects of group status are confounded in most BFLPE studies. For the verbal domain, no study has yet investigated contrast and assimilation effects simultaneously. Strong assimilation effects can be assumed for gifted ability grouping. Aims: We aimed at disentangling contrast and assimilation effects of full‐time within‐school gifted tracking on verbal ASC and math ASC. Sample: Students attended regular or gifted classes within the top track of German secondary schools. Our sample comprised 1, 330 fifth‐grade students (42 regular classes, n  =   1, 069, 48% female; 15 gifted classes, n  =   261, 39% female). Methods: Using multilevel regression analyses, we simultaneously modelled negative contrast effects of class ability and positive assimilation effects of class type (regular vs. gifted) on ASC in math and the verbal domain. Results and conclusions: In the mathematical domain, the assimilation effect, caused by membership in gifted classes, compensated for negative contrast effects of class‐average achievement on ASC even after controlling for previous ASC. In the verbal domain, we found neither a significant contrast effect nor an assimilation effect. Implications for gifted education are discussed.